Analisis Tren Nilai Tukar Petani Antar Subsektor Pertanian Di Provinsi Sulawesi Utara - Katadi Saraba, Angel; Waney, Nordy Fritsgerald Lucky; Rumagit, Grace Adonia Josephine (Sam Ratulangi University, 2024)
This study aims to analyze the trend of Farmer Exchange Rate between five agricultural subsectors in North Sulawesi Province in 2013-2022. The data collection method in this research is the secondary data survey method. This research uses time series data in 2013-2022 obtained from the North Sulawesi Central Bureau of Statistics. Data analysis in this study used trend analysis with the least square method. The results showed an increasing trend in the five subsectors in the future. The trend analysis formula formed in the food crop subsector is 98.10 + 0.38x, in the horticulture subsector is 101.55 + 0.41x, in the plantation subsector 96.85 + 0.46x, in the livestock subsector is 102.21 + 0.28x, and in the fisheries subsector is 104.049 + 0.34x. The subsector that showed the highest increase was the plantation subsector. The subsector that experienced the lowest increase was the livestock subsector.